A New Antiviral Regimen Against SARS-CoV-2 Based on Nanoviricide’s Biopolymer (NV-CoV-2) - Chakraborty, Ashok; Diwan, Anil; Barton, Randall; Arora, Vinod; Thakur, Yogesh; Chiniga, Vijetha; Tatake, Jay; Pandey, Rajesh; Holkar, Preetam; Holkar, Neelam; Pond, Bethany (Frontiers in Nanotechnology, 2022)
NV-CoV-2, a nanoviricide composed of covalently attached polyethylene glycol and alkyl pendants that are designed to bind free virion particles of multiple strains of coronaviruses in a broad-spectrum manner at multiple points. The binding interaction is like a nano-velcro-tape and may cause a lipid–lipid fusion between nanoviricide micelle and the lipid envelope of the virus. A nanoviricide can encapsulate the virus and dismantle it without any involvement of the host immune system, ultimately disabling the infectibility of the host cells. Thus, it may be expected to count a stronger and synergistic antiviral effect by combining NV-CoV-2 with other anti-coronavirus regimens like remdesivir. Furthermore, some ligands similar to the SARS-CoV S-protein are designed by molecular modeling and attached to the nanoviricide at the same site as where the cognate cellular receptor, ACE2, binds. As a result, a competitive binding inhibition may occur. A nanoviricide can encapsulate other antiviral compounds and protect them from serum-mediated degradation in vivo. This makes the antiviral compounds available for a longer period of time to interact with RNA polymerase and inhibit it. Altogether, a multipoint antiviral efficacy can be achieved with our nanoviricide, NV-CoV-2.